EFFECTIVENESS OF BADUNG’S REGIONAL HOUSE OF REPRESENTATIVE SUPERVISION ON TOURISM INVESTMENT - I Gede Ardian Paramandika; I Made Arjaya; I Ketut Kasta Arya Wijaya (Jurnal Scientia, 2023)
Badung Regency is one of the destinations for tourism investment, but the amount of investment that goes to Badung Regency must be supervised by the Representative House of Badung Regency. The research aiming on examining effectiveness of supervision of the Representative Council of Badung Regency on tourism investment.The research was done using empirical legal research with legal sociology approach by conducting interviews with informants. Results implies that, the Representative Council of Badung Regency as an element of regional administration has the authority to supervise investment in the tourism sector by supervising the Badung Regency Lisencing Agency through Commission II. Technical supervision is carried out in the Control and Executor Sector by forming a monitoring and coaching team for tourism business actors. The strategy used in overcoming obstacles related to investment supervision and increasing investment is to provide guidance through technical guidance with several sources and provide incentives to business actors who contribute to the development of Badung Regency.